2023
DOI: 10.1038/s41467-023-37424-w
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose IL-2 enhances the generation of IL-10-producing immunoregulatory B cells

Abstract: Dysfunction of interleukin-10 producing regulatory B cells has been associated with the pathogenesis of autoimmune diseases, but whether regulatory B cells can be therapeutically induced in humans is currently unknown. Here we demonstrate that a subset of activated B cells expresses CD25, and the addition of low-dose recombinant IL-2 to in vitro stimulated peripheral blood and splenic human B cells augments IL-10 secretion. Administration of low dose IL-2, aldesleukin, to patients increases IL-10-producing B c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…Therefore, it is unlikely that unstimulated B-cells provide additional activation stimulus or inhibition to T-cells in the co-culture ( Supplementary Figure 3 ). It has been demonstrated that low-dose IL-2 can promote the differentiation of regulatory B-cells, although CpG pre-stimulation (ODN2395) is required for the induction of IL-10 producing B-cells by low dose IL-2 which could inhibit the TNF-α production of CD4 T-cells in a co-culture of B-cells and T-cells in 1: 5 ratio ( 97 ). Accordingly, in our experiments CpG stimulation (ODN2006) in combination with CytoStim (CS) and IL-2 decreased CD25-positivity of T-cells by only 9% compared to CS+IL-2 stimulated T-cells (71.9 vs. 62.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is unlikely that unstimulated B-cells provide additional activation stimulus or inhibition to T-cells in the co-culture ( Supplementary Figure 3 ). It has been demonstrated that low-dose IL-2 can promote the differentiation of regulatory B-cells, although CpG pre-stimulation (ODN2395) is required for the induction of IL-10 producing B-cells by low dose IL-2 which could inhibit the TNF-α production of CD4 T-cells in a co-culture of B-cells and T-cells in 1: 5 ratio ( 97 ). Accordingly, in our experiments CpG stimulation (ODN2006) in combination with CytoStim (CS) and IL-2 decreased CD25-positivity of T-cells by only 9% compared to CS+IL-2 stimulated T-cells (71.9 vs. 62.9%).…”
Section: Discussionmentioning
confidence: 99%
“…72 In addition to these generalized effects, IL-10 produced by Bregs, as other sources of IL-10, favors the formation of Tregs, which can then amplify the regulatory microenvironment, suppressing in particular proinflammatory T-cell subsets. [73][74][75] The resulting tolerogenic environment has the potential to then lead to a systemic tolerance toward atherosclerosis-associated antigens, an idea explored in detail in several vaccine trials (see following section). The interaction between Tregs and B cells in atherosclerosis is likely an ongoing process, as Tregs may continue to interact with B cells in tertiary lymphoid organs (TLOs) after induction, potentially leading to the emergence of clones with enhanced specificity for disease-associated antigens.…”
Section: Antibody-independent B-cell Interactionsmentioning
confidence: 99%
“…Low-dose IL-2 has been shown to induce Tregs in humans, as seen in the LILACS trial (Low-Dose Interleukin-2 in Patients With Stable Ishcaemic Heart Disease and Acute Coronary Syndromes), 75 with further analysis showing an increase in plasmablast populations enriched for a Breg gene signature. 73 Furthermore, treatment of human peripheral blood and splenic B cells with IL-2 in vitro increases IL-10 secretion 73 through the inhibition of BACH2 (BTB domain and CNC homolog 2), a transcriptional repressor that binds to the IL-10 promoter region, with further in vivo evidence of significant downregulation of BACH2 in patients treated with low-dose IL-2. Recently, a large phase II double-blinded placebo-controlled clinical trial investigating the impact of low-dose IL-2 on vascular inflammation post-MI (IVORY [Low-Dose Interleukin 2 for the Reduction of Vascular Inflammation in Acute Coronary Syndromes]) 80 concluded that a potentially important subanalysis is evaluation of whether IL-2–induced Bregs are associated with a reduction in vascular inflammation.…”
Section: Antibody-independent B-cell Interactionsmentioning
confidence: 99%
“…In fact, it has been shown that IL-2 regulates the expression of Foxp3 in human Treg cells via STAT3 and STAT5 [ 38 ]. More recently, also distinct B-cell subsets have been shown to express CD25, which utilize low-dose IL-2 to differentiate into B regulatory cells (Breg) [ 39 ]. Conversely, deficiency of IL-2Rα as observed in patients, similar to Il2ra −/− mice, was found to be associated with overshooting lymphoproliferation and lymphocytic infiltration of multiple organs (lung, liver, and skin) with oligoclonal T cells.…”
Section: Distinct Monoclonal Antibodies Shape the Function And Increa...mentioning
confidence: 99%